Labour protection for the vulnerable: An evaluation of the salary and injury claims system for migrant workers in Singapore - FILLINGER, Tamera (Institutional Knowledge at Singapore Management University, 2017)
This research seeks to review and analyze the protections afforded to migrant workers in Singapore who bring salary and injury claims to the Ministry of Manpower for resolution. Our focus is male Work Permit holders from Bangladesh, China, and India who make up the majority of the workforce in Singapore’s construction and marine sectors. Work Permit holders are the lowest wage category of foreign workers and comprise nearly a third of the overall workforce. While these workers play an important role in building the nation, they face workplace issues that many would not associate with a modern economy.